Children’s programming before and after DTT implementation in Spain - Medina, Mercedes; Herrero, Mónica; Etayo, Cristina (Ámbitos. Revista Internacional de Comunicación, 2019)
With the privatization of television in the nineties, the television schedules were dominated by light entertainment designed to maximize audiences. As a consequence, children’s programming almost disappeared from the free-to-air channels and television consumption among children decreased. That is why children programming became one of factors to pay for television. However, thanks to the DTT, the offer for children increased. The purpose of this paper is in one hand to inquire if a wider offer of channels has brought more channels for children and if they have impacted in the consumption of television by children, and secondly, if children programming still play a significant role to pay for television. The results confirm that the increase of specialized children channels produced an increment of the children television consumption.